Small-Scale Spatial Variability of Soil Chemical and Biochemical Properties in a Rewetted Degraded Peatland - Negassa, Wakene; Baum, Christel; Schlichting, Andre; Müller, Jürgen; Leinweber, Peter (Frontiers in Environmental Science, 2019)
There is indication in the literature that degradation of natural peatlands reduced spatial variability of soil chemical and biochemical properties. However, we lack empirical data on the impact of rewetting peatland on the spatial variability of these properties. To investigate the spatial variability of the soil properties, we collected soil samples from the depths of 0-10 cm and 10-20 cm in a rewetted peatland of northern Germany. Overall, we collected 50 samples from 50 grid cells, and the area of each grid cell was 9.0 m2. We measured 34 important soil chemical and biochemical properties and evaluated the data with descriptive and geospatial statistical analyses. The concentrations of most plant available nutrient elements were low with high coefficients of variation (CV) that ranged from 15 to 117%, whereas the CV of most of the total and oxalate extracted elements was 15% CV. The degree of phosphorus (P) saturation (DPS) and P saturation ratio (PSR) were 11% and 0.05, which were low as compared to the threshold levels of 25% DPS and 0.11 PSR for mineral and wetland soils. The microbial biomass C and N ranged from 389 to 2463 mg kg-1 and 32 to 215 mg kg-1 at the depth of 0-10 cm and from 343 to 1570 mg kg-1 and 14 to 160 mg kg-1 at the depth of 10-20 cm, respectively. Similarly, the dehydrogenase and -glucosidase activities were lower by 76 and 61% at the soil depth of 10-20 cm compared to the upper 10 cm. The geospatial statistical analysis revealed that 87% of the soil chemical properties were spatially correlated and 85% of the spatial correlation was strong with less than 0.20 nugget to sill ratio at 5 to 12 m ranges. Similarly, 86 and 71% of the biochemical properties were strongly spatially correlated at the depth of 0-10 and 10-20 cm, respectively, with 0.16 nugget to sill ratio at the short ranges (4 to 6 m). The strong spatial correlation of most of the soil chemical and biochemical properties at short ranges indicate the high variability of the rewetted peatland.